IgG2 subclass restriction of antibody to pneumococcal polysaccharides. - Barrett, D J (1986)
Studies in experimental animals suggest that antibody responses to certain polysaccharide antigens may be restricted in IgG subclass distribution. To determine if human antibodies to pneumococcal polysaccharides are similarly restricted we measured the IgG subclass specific response to immunization with purified polyvalent pneumococcal polysaccharide vaccine. For the type 3 pneumococcal antigen, the geometric mean titre of IgG2 antibody was significantly greater than that of IgG1, IgG3 or IgG4, in both pre-immunization and post-immunization sera. A significant rise in mean titre, comparing pre- to post-immunization sera was observed only for IgG2 antibody. Similar predominance of IgG2 antibody was found for pneumococcal polysaccharides types 6, 18, 19 and 23. In contrast, antibody to the protein antigen tetanus toxoid was exclusively of the IgG1 subclass. Patients with IgA/IgG2 deficiency demonstrated a normal IgG response to tetanus, a normal IgM response to pneumococcal polysaccharides, but no IgG antibody to pneumococcal antigens. IgG2 subclass restriction of antibody to pneumococcal polysaccharides suggest that these antigens may elicit an immune response analogous to the murine type 2 T-cell independent immunogens which show IgG subclass restriction and the requirement of a mature B cell subset defined by the Lyb5+ alloantiserum. Our findings support the possibility of subclass-specific inducing or regulating mechanisms for human responses to carbohydrate or polysaccharide antigens.